Influence of Groove Design on the Mechanical Properties of AISI 1018 Mild Steel Welded Joints - Durowaye, Stephen; Ayoolaa, Wasiu; Hammed, Olalekan; Lawal, Ganiyu (Kathmandu University Journal of Science, Engineering and Technology, 2023)
The influence of groove design on mechanical properties of AISI 1018 mild steel welded joint was studied. An 8 mm thick mild steel plate was marked out and cut to dimension of 120 × 75 × 8 mm using a portable cutting machine. Groove preparation was done for the single-V and single-beveled grooves. After proper alignment of the edges, the work pieces were welded using the Shielded Metal Arc Welding (SMAW) method with a Direct Current (D.C.) welding machine with voltage and current of 220 V and 100 A respectively. Specifically, gauge-12 (2.5 mm) stick electrodes were used for the root run while many passes (hot pass, filling and capping) were undertaken with gauge-10 (3.25 mm) electrodes because of the volume of filler metal required to fill the single-V and single beveled joints. The mechanical properties of the butt, single beveled and singe V joints were evaluated. The results showed that microstructural changes occurred in the specimens due to heat in the fusion and heat-affected zones with the appearance of ferrite, pearlite, martensite and bainite phases with grain boundaries, which confirm recrystallization. The heat-affected zone single V-joint exhibited the highest tensile strength of 442.41 MPa while fusion zone single V-joint exhibited the highest hardness of 358.9 HV. In fusion zone, the butt-joint specimen exhibited impact energy of 65.2 J/mm2 compared to 62.37 J/mm2 and 48.81 J/mm2 exhibited by the single V and single beveled joints respectively. However, the heat-affected zone single V-joint exhibited the highest impact energy of 73.22 J/mm2.